2011
DOI: 10.1007/s00421-011-2202-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a soccer match on the cardiac autonomic control of referees

Abstract: The purpose of this study was to assess the effect of a soccer match on the cardiac autonomic control of heart rate (HR) in soccer referees. Sixteen Spanish regional and third division referees (11 males: 26 ± 7 years, 74.4 ± 4.1 kg, 178 ± 3 cm, Yo-Yo IR1 ~600-1,560 m; 5 females: 22 ± 3 years, 59.3 ± 4.8 kg, 158 ± 8 cm, Yo-Yo IR1 ~200-520 m) participated with 24-h HR recordings measured with a Polar RS800 during a rest and a match day. Autonomic control of HR was assessed from HR variability (HRV) analysis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
20
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
(69 reference statements)
7
20
0
3
Order By: Relevance
“…Interestingly, when shorter periods of HRV were analyzed (i.e., hour to hour), flight-related stress was accompanied by a vagal withdrawal within the hour prior to take-off and was maintained for up to 2 h after destination arrival. This reduction in HRV with flight stress was previously noted in experienced (Oliveira-Silva and Boullosa, 2015) and novice military pilots (Sauvet et al, 2009) and reinforces that anticipatory autonomic responses occur prior to an announced stress (Hynynen et al, 2009; Boullosa et al, 2012). It is well known that adaptation in the face of stress is a major priority for all organisms (Ulrich-Lai and Herman, 2009) with an autonomic anticipatory change occurring in response to an expected biological stress (Boullosa et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, when shorter periods of HRV were analyzed (i.e., hour to hour), flight-related stress was accompanied by a vagal withdrawal within the hour prior to take-off and was maintained for up to 2 h after destination arrival. This reduction in HRV with flight stress was previously noted in experienced (Oliveira-Silva and Boullosa, 2015) and novice military pilots (Sauvet et al, 2009) and reinforces that anticipatory autonomic responses occur prior to an announced stress (Hynynen et al, 2009; Boullosa et al, 2012). It is well known that adaptation in the face of stress is a major priority for all organisms (Ulrich-Lai and Herman, 2009) with an autonomic anticipatory change occurring in response to an expected biological stress (Boullosa et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…This reduction in HRV with flight stress was previously noted in experienced (Oliveira-Silva and Boullosa, 2015) and novice military pilots (Sauvet et al, 2009) and reinforces that anticipatory autonomic responses occur prior to an announced stress (Hynynen et al, 2009; Boullosa et al, 2012). It is well known that adaptation in the face of stress is a major priority for all organisms (Ulrich-Lai and Herman, 2009) with an autonomic anticipatory change occurring in response to an expected biological stress (Boullosa et al, 2012). As the participants of the present study were passengers that had accumulated < 50 flying hours on commercial airlines, the anticipatory response could have been associated with flight inexperience (Waterhouse et al, 2002; Hynynen et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…For the computation of YYIR1 test global means, SDs and quantiles (Figure 2), 239 studies or subgroups with a total of 4,726 participants (median of reported age means = 21.1, inter quartile range [IQR] of reported age means = 17.8–24.5 years) were used (Krustrup and Bangsbo, 2001; Krustrup et al, 2003; Mohr et al, 2003, 2010, 2016; Weston et al, 2004; Castagna et al, 2005, 2006b, 2008; Atkins, 2006; Thomas et al, 2006; Rampinini et al, 2007, 2008, 2010; Mujika et al, 2009; Ben Abdelkrim et al, 2010; Chaouachi et al, 2010; Dupont et al, 2010; Veale et al, 2010; Wong et al, 2010; Buchheit et al, 2011; Chtourou et al, 2011; Chuman et al, 2011; Cobley et al, 2011; Markovic and Mikulic, 2011; Matthys et al, 2011; Roberts et al, 2011; Spencer et al, 2011; Ueda et al, 2011; Alemdaroglu et al, 2012; Boullosa et al, 2012, 2013a,b; Cihan et al, 2012; Cone et al, 2012; Deprez et al, 2012, 2014, 2015a,b; Heaney, 2012; Ingebrigtsen et al, 2012, 2014; Lim, 2012; Scanlan et al, 2012, 2014; Shalfawi et al, 2012, 2013; Teplan et al, 2012a,b, 2013; Vernillo et al, 2012; Berdejo-del-Fresno and González-Ravé, 2013; Cullen et al, 2013; Faude et al, 2013; Higham et al, 2013; Idrizovic and Raickovic, 2013; Manzi et al, 2013; Oliveira et al, 2013; Román-Quintana et al, 2013; Wylie et al, 2013; Yuki et al, 2013; Casamichana et al, 2014, 2015; Clarke et al, 2014; Fabregat-Andres et al, 2014; Fanchini et al, 2014, 2015a,b; Hammouda et al, 2014; Hermassi et al, …”
Section: Resultsmentioning
confidence: 99%
“…Similar HRV changes have been reported in various athlete populations immediately before competition with parasympathetic withdrawal associated with pre-competition anxiety [ 9 , 25 ] . Recently, it was reported that sub-elite soccer referees exhibited lower daytime HRV (12:00-17:00) prior to a soccer match compared to a non-match day [ 4 ] . Emotional or psychological stresses including mental preparation for competition may have heightened sympathetic and/or reduced parasympathetic modulations resulting in lower HRV for referees [ 4 ] and the current players prior to competition.…”
mentioning
confidence: 99%
“…Recently, it was reported that sub-elite soccer referees exhibited lower daytime HRV (12:00-17:00) prior to a soccer match compared to a non-match day [ 4 ] . Emotional or psychological stresses including mental preparation for competition may have heightened sympathetic and/or reduced parasympathetic modulations resulting in lower HRV for referees [ 4 ] and the current players prior to competition. It remains to be seen whether such autonomic stimulation is detrimental to game performance with future studies needed to examine this response over many weeks and games in a competitive season.…”
mentioning
confidence: 99%